CONTAINING FEELINGS OF ATTITUDE TO WORK IN CHILDREN’S FOLKLORE - Abdulbokiyeva Moxichehra Hamidulla qizi (Research Focus International Scientific Journal, 2022)
Children play with words and learn from the steps of spiritual maturity. A child is far from understanding the meaning of words at the first stage of his development. However, he enters the magical world of words while playing with them. In order to satisfy this spiritual need in children, adults sometimes invented spiritual games such as riddles and quick sayings. The children liked them very much and really adopted them and even made them their own.